Intellectual Capital, Good Corporate Governance, Pengungkapan Corporate Social Responbility dan Kinerja Keuangan Perusahaan - Dumanauw, Olive Gracely; Agung Suaryana, I Gusti Ngurah (E-Jurnal Akuntansi, 2021)
This study was conducted to examine the effect of intellectual capital, good corporate governance and disclosure of corporate social responsibility on the financial performance of companies listed on the Indonesia Stock Exchange for the 2014-2016 period. This research is associative research. The population of this study was 90 companies and was observed during 2014 to 2016. The sampling technique used in this study was purposive sampling. Based on this technique, 30 companies were obtained as samples. The data collection method used in this study is a non-participant observation method. The researcher used multiple linear regression as an analysis technique. Based on the results of the analysis, it can be concluded that Intellectual Capital has no effect on financial performance, good corporate governance and disclosure of corporate social responsibility influences financial performance. Keywords: Intellectual Capital; Good Corporate Governance; Corporate Social Responsibility; Financial Performance.